2014
DOI: 10.1039/c3nr05081e
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired formation of functional calcite/metal oxide nanoparticle composites

Abstract: Biominerals are invariably composite materials, where occlusion of organic macromolecules within single crystals can significantly modify their properties. In this article, we take inspiration from this biogenic strategy to generate composite crystals in which magnetite (Fe 3 O 4 ) and zincite (ZnO) nanoparticles are embedded within a calcite single crystal host, thereby endowing it with new magnetic or optical properties. While growth of crystals in the presence of small molecules, macromolecules and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…The optical and magnetic functionalizations are achieved through nanoparticle incorporation inside the single crystals. [48] This work creates a novel and facile pathway to design functionalized single-crystalline materials to expand their potential applications. In contrast to other mechanisms of particle incorporation that are associated with fast crystallization and/or crystal-particle mutual wetting, [47] the gel-mediating strategy described here allows a wide range of particles to be incorporated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The optical and magnetic functionalizations are achieved through nanoparticle incorporation inside the single crystals. [48] This work creates a novel and facile pathway to design functionalized single-crystalline materials to expand their potential applications. In contrast to other mechanisms of particle incorporation that are associated with fast crystallization and/or crystal-particle mutual wetting, [47] the gel-mediating strategy described here allows a wide range of particles to be incorporated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Afterwards, Garcia-Ruiz et al found that gelgrown protein (lysozyme, ferritin and thaumatin) crystals also incorporate gel (silica and/or agarose) matrix [5,8,9]. More recently, calcite, again, were shown to incorporate gelatine [10], poly-acrylamide [11], agarose [12][13][14][15] and xyloglucan gels [16]. Although the total amount is still very limited as compared with the large amount of gel-grown crystals, the examples of gelincorporated single-crystals are increasing [17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…34,35,57 The encapsulation of inorganic and metallic guest particles has only been achieved by functionalizing the nanoparticles with diblock copolymers, 58,59 or immobilizing them within hydrogel matrices. 39,40 In all of these cases, the encapsulated nanoparticles are surrounded by an insulating organic layer at the interface between the guest nanoparticle and the host crystalline material. In electronic materials, such an insulating layer would be a barrier to the transport of carriers between the two crystalline materials.…”
Section: Encapsulation Of Particles In Single Crystals the Confinemementioning
confidence: 99%
“…34 This approach has been widely demonstrated for single crystal carbonates, where the encapsulation of organic colloids, 35 micelles, 36,37 and fibers 38 has been achieved by the vapor diffusion of ammonium carbonate into an aqueous matrix (e.g., dispersion of particles or hydrogel) containing dissolved alkali metal salts. 39,40 As an extension of this approach, we hypothesized that a solution-vapor phase crystallization of an oxide (e.g., Cu 2 O) could be accomplished by the diffusion of a low vapor pressure basic species or reducing agent 41 into a transition metal oxide salt solution with the application of heat to drive the system to the oxide phase. 42 Experimental Design.…”
Section: Introductionmentioning
confidence: 99%